Selected Physical, Colour and Textural Characteristics of Market Rasogolla - K., Srinivasa; Barnwal, Pradyuman; Singh, Pritpal (Indian Journal of Dairy Science, 2017)
Rasogolla is regarded as the king of Indian milk sweets. The various characteristics such as physical (size, unit weight, juiciness and porosity), colour and textural quality characteristics of Rasogolla plays a vital role in its marketing and consumer acceptance. In present study, physical, colour and textural quality characteristics of six brands of market Rasogolla were determined. The size, geometric mean diameter, varied from 2.7Â±0.0 mm to 3.9Â±0.1 cm. All physical and colour characteristics of market Rasogolla were found statistically highly significant (p